The Immunisation Dilemma – Part 3.1 - Golden, Isaac; Stranieri, Andrew (Homœopathic Links, 2014)
An international survey was conducted to obtain evidence regarding the attitudes towards and use of homœoprophylaxis (HP) by accredited homeopaths. In addition, a survey of positions on HP by homeopathic associations around the world was conducted. General conclusions about the extent of agreement or disagreement regarding HP will be derived from the results of both surveys. These findings will inform us of the next step in a process towards an international position statement on HP.
Keywords: Homœoprophylaxis; Vaccination; Survey